Benarkah Suku Bunga Memengaruhi Volatilitas Pasar Saham Syariah? - Septiana Indarwati (Journal of Islamic Economics and Finance Studies, 2021)
AbstractThis research attempts to explore to what extent the sensitivity volatility of Islamic stock markets in Indonesia toward macroeconomics. The writer examines inflation, exchange rates, money supply (JUB), interest rates (BIRATE), and Industrial Production Index (IPI) as part of the macroeconomic variables. Meanwhile, the writer also uses Jakarta Islamic Index (JII) as the measurements for Islamic stock markets. This research uses the calculation of the stock return volatility based on the Generalized Autoregressive Conditional Heteroscedasticity (GARCH (2, 1)) combined with Regressive Distributed Lag (ARDL) analysis. The writer uses monthly data from Indonesia Stock Exchange, starting from January 2006 to December 2019 as part of the data collection. This research found that BIRATE has a negative effect on the conventional stock market while the Islamic stock market has a positive and insignificant effect on the level α = 5%.  It points out the Islamic principles that the interest rate is not a significant variable in explaining the stock market’s volatility. According to the finding of this research, the writer argues that stabilizing interest rates will not significantly impact the volatility of the Islamic stock market.AbstrakPenelitian ini mencoba untuk mengeksplorasi sejauh mana sensitivitas volatilitas pasar saham syariah di Indonesia terkait dengan ekonomi makro. Penulis menggunakan inflasi, nilai tukar rupiah, penawaran uang (JUB), suku bunga (BI rate) dan Indeks Produksi Industri (IPI) sebagai pengukuran dari ekonomi makro. Sementara itu, penulis menggunakan Jakarta Islamic index (JII) sebagai pengukuran pasar saham syariah. Penelitian ini menggunakan perhitungan volatilitas return saham dengan Generalized Autoregressive Conditional Heteroskedasticity (GARCH (2, 1) dikombinasikan dengan Analisis Autoregressive Distributed Lag (ARDL). Pengumpulan data dalam penelitian ini menggunakan data bulanan dari Bursa Efek Indonesia dari bulan Januari 2006 sampai Desember 2019. Penelitian ini menemukan bahwa, variable BI Rate tidak berpengaruh signifikan terhadap pasar saham syariah pada taraf α=5%. Ini menyoroti prinsip-prinsip Islam bahwa tingkat bunga bukanlah variabel yang signifikan dalam menjelaskan volatilitas pasar saham. Menurut temuan pada penelitian ini, penulis memberikan dukungan lebih lanjut bahwa menstabilkan suku bunga tidak akan berdampak signifikan pada volatilitas pasar saham syariah.